The emergence and functioning of the modern global ranking system for higher education institutions - Allamyradov, Meylis Annaorazovich; Seyitliev, Kerimberdi Ovezberdievich; Amanseyidov, Shamuhammet Halmuhammedovich; Dzhaparov, Tuvakmammet; Orazberdiev, Serdar Yazmiradovich (Современное образование, 2025)
This paper examines the prerequisites for the emergence and stages of formation of the modern global higher education institution rankings system. It analyzes the key reasons that necessitated an objective assessment of the quality of university education at a global level, including the processes of internationalization, increased competition among universities, and the demands from employers and prospective students. Particular attention is paid to the main international rankings, their methodologies, evaluation criteria, and impact on the development of universities. Both positive and problematic aspects of the functioning of ranking systems are discussed, including their influence on university strategy, academic mobility, funding, and research activities. Globalization has intensified competition among universities, leading to an increased significance of international rankings. These rankings affect the prestige of universities, students' choice, development strategies, and the global education market. Global university rankings enhance competition, influence academic reputation, investments, and international image. They become tools for attracting students, scientific capital, and strengthening educational exports. The analysis shows that the effectiveness and quality of a higher education institution's activities in most authoritative rankings are assessed based on a combination of key areas of its functioning, among which particular importance is given to educational, research, international, and entrepreneurial activities, including the commercialization of scientific developments. British researcher M. Clarke specifies the logistics of educational choice by proposing a three-tiered decision-making model characteristic of prospective students oriented towards global educational markets. This approach seems justified. At the same time, empirical data allow for the addition of a fourth element to this scheme, particularly relevant for applicants to master's and doctoral programs. This additional stage may involve the choice of a specialized faculty or department within an already formed pool of universities. Such a choice is usually based on the scientific reputation of the department, rankings in subject areas, and the presence of leading research schools. Therefore, the structure of educational choice in the context of the internationalization of higher education takes on a multi-level character. In conclusion, the role of rankings as a tool for the global positioning of universities is emphasized, as well as the necessity for their further enhancement taking into account the regional context and the specificities of educational systems.